2007
DOI: 10.1063/1.2760169
|View full text |Cite
|
Sign up to set email alerts
|

Deoxyribonucleic acid-based photochromic material for fast dynamic holography

Abstract: The authors report on a biopolymeric material made of deoxyribonucleic acid ͑DNA͒ complexed with the cationic surfactant cetyltrimethyl-ammonium ͑CTMA͒ and doped with the photochromic disperse red 1 dye ͑DR1͒ for dynamic holographic recording. The molar ratio of the DNA-CTMA to the dye is about 5:1. They have found that the photochromic properties of DR1 in the DNA-CTMA matrix are favorably modified in speed of response with respect to conventional polymeric matrices. Dynamic holographic gratings which were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 20 publications
1
30
0
Order By: Relevance
“…This study also aimed to discover and study new substances with different types of proteins containing in the albumins for the manufacture of volume transmission holograms. Through more research, these substances will compete with the already reported results [21]- [23].…”
Section: Introductionmentioning
confidence: 84%
“…This study also aimed to discover and study new substances with different types of proteins containing in the albumins for the manufacture of volume transmission holograms. Through more research, these substances will compete with the already reported results [21]- [23].…”
Section: Introductionmentioning
confidence: 84%
“…e l s e v i e r . c o m / l o c a t e / o p t m a t used for the investigation of fast response, such as all-optical switching [24][25][26]. Here, in order to explore the potential of DR1 to be attractive for optical memory applications, the short lifetime of the cis state should be enhanced by doping it into proper solid matrix to slow down the rate of the cis-trans isomerization.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 98%
“…However, investigated azo-polymers are different and their behavior under the same illumination conditions can differ depending on specific material properties and chemistry (type of bonds, way of substitutions and different azo-chromophores) involved. Various groups of materials containing azo-benzene derivative molecules have also been investigated including glasses [13], liquid crystalline polymers [14,15], biopolymers [16][17][18][19], liquid crystals [20][21], Langmuir-Blodgett-Kuhn structures [22,23], layer-by-layer films [ 24,25] monolayers [26,27] and even nano-objects [28,29]. Particularly interesting is light-induced macroscopic polymer mass transport discovered initially for azo-substituted polymers [30,31].…”
Section: Introductionmentioning
confidence: 99%